MorePork - Study: Food Demand and Nutrition Cross-Sectional Survey - Ouma, Emily; Pezo, Danilo; Dione, Michel; Lukuyu, Ben; Marshall, Karen; Lule, Peter; Asiimwe, Grace; Opio, Felix; Kawuma, Brian; Kariuki, Eunice (International Livestock Research Institute, 2023)
MorePork: More pork by and for the poor: Catalyzing emerging smallholder pig value chains in Uganda for food security and poverty reduction The project seeks to test and pilot best bet options to improve on-farm productivity, household nutrition and pork safety in the marketing chain, so that benefits are enhanced for poor men and women farmers and their organisations, market actors and consumers, while minimizing negative environmental impacts., The objective of this study is to assess households' food demand and nutritional security with consideration for intra-household resource and food allocation. This involved socio-economic status with a focus on access and use of productive assets especially in livestock production, demand, availability, actual access to and control over adequate food by household members and dietary survey survey (children, men & women) to assess intra-household food distribution patterns and lastly, anthropometric survey (children, men & women) assesses which HH members are at higher nutrition risk.